5th Young Scientists Congress Secretariat, Bangladesh Academy of Sciences (BAS)National Science and Technology, at 25-27 November 2022, attended 2022, Complex, Agargaon, Dhaka, Bangladesh (The Journal of Ad-din Women's Medical College, 2023)
Abstract not available  The Journal of Ad-din Women's Medical College; Vol. 10 (2), July 2022; p 63-66